Exploring the temporal dynamics of rumen bacterial and fungal communities in yaks (Bos grunniens) from 5 days after birth to adulthood by full-length 16S and 18S rRNA sequencing - Yang, Shuli; Zhang, Guangrong; Yuan, Zaimei; He, Shichun; Wang, Rongjiao; Zheng, Jieyi; Mao, Huaming; Chai, Jianmin; Wu, Dongwang (Frontiers in Veterinary Science, 2023)
The rumen of ruminants is inhabited by complex and diverse microorganisms. Young animals are exposed to a variety of microorganisms from their mother and the environment, and a few colonize and survive in their digestive tracts, forming specific microflora as the young animals grow and develop. In this study, we conducted full-length sequencing of bacterial and fungal communities in the rumen of pastured yaks of different ages (from 5 days after birth to adulthood) using amplified sequencing technology. The results showed that the rumen microflora of Zhongdian yaks changed gradually from 5 to 180 days after birth and tended to stabilize at 2 years of age. The rumen of adult yaks was the most suitable for the growth and reproduction of most bacteria. Bactria diversity of the yak rumen increased gradually from 5 days after birth to adulthood. With the growth of yaks, different dominated bacteria were enriched in different groups, but Prevotella remained highly abundant in all groups. The yak rumen at 90 days of age was the most suitable for the growth and reproduction of most fungi, and 90 days of age could be a cut-off point for the distribution of fungal communities. Fungal Thelebolus was the firstly reported in yak rumen and was enriched in the yak rumen of 90 days after birth. The most abundant and balanced fungal genera were found in adult yaks, and most of them were only detected in adult yaks. Our study reported on the rumen bacterial and fungal communities of Zhongdian yaks grazed at different ages and provided insights into the dynamic changes of dominant microflora with yak growth.